Learning Clinical Reasoning: The Experience of Postgraduate Psychiatry Trainee Doctors in Qatar - Dalia Albahari (17115664) (2023)
Phenomenon As a core competency in medical education, clinical reasoning is a pillar for reducing medical errors and promoting patient safety. Clinical reasoning is a complex phenomenon studied through the lens of multiple theories. Although cognitive psychology theories transformed our understanding of clinical reasoning, the theories fell short of explaining the variations in clinical reasoning influenced by contextual factors. Social cognitive theories propose a dynamic relationship between learners’ cognitive process and their social and physical environments. This dynamic relationship highlights the essential role of formal and informal learning environments for learning clinical reasoning. Approach My research aimed to explore the personal experience of learning clinical reasoning in a sample of postgraduate psychiatry trainee doctors using cognitive psychology and social cognitive theories. A stratified convenience sample of seven psychiatry trainee doctors working in the Mental Health Services in Qatar completed semi-structured interviews in 2020. I analyzed the data manually using theoretical thematic analysis. Findings I identified three overarching themes with multiple subthemes. The first theme was the hierarchical cultural impact on perceived learning opportunities and learning behavior. The first theme had two subthemes that explored the relationship with team members and the expected hierarchy roles. The second theme was the impact of emotions on the learning and execution of clinical reasoning.The second theme had three subthemes that explored the personal approach to managing emotions related to perceived self-efficacy and professional image. The third theme was characteristics of learning environments and their role in learning clinical reasoning. The last theme included three subthemes that explored stressful, autonomous, and interactive environments. Insights The results accentuate the complexity of clinical reasoning. Trainees’ experience of learning clinical reasoning was influenced by factors not controlled for in the curricula. These factors constitute a hidden curriculum with a significant influence on learning. Our local postgraduate training programmes will benefit from addressing the points raised in this study for effective and culturally sensitive clinical reasoning learning. Other Information Published in: Teaching and Learning in Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/10401334.2023.2209076